The best backbone for HIV prevention, treatment, and elimination: Emtricitabine+tenofovir. Issue 1 (5th May 2022) - Schinazi, Raymond F; Patel, Dharmeshkumar; Ehteshami, Maryam
The advent of antiretroviral combination therapy has significantly impacted the HIV/AIDS epidemic. No longer a death sentence, HIV infection can be controlled and suppressed using cocktail therapies that contain two or more small molecule drugs. This review aims to highlight the discovery, development, and impact of one such molecule, namely, emtricitabine (FTC, emtriva), which is one of the most successful drugs in the fight against HIV/AIDS and has been taken by over 94% of individuals infected with HIV in the USA. We also pay tribute to Dr. John C. Martin, former CEO and Chairman of Gilead Sciences, who unexpectedly passed away in 2021. A true visionary, he was instrumental in delivering FTC, as part of combination therapy with TDF (tenofovir, viread) to the global stage. As the fight to eradicate HIV marches on, we honor Dr. Martin's legacy of collaboration, achievement, and hope.